Contribution of different etiology factors in fading pregnancy occurrence - M. Lozynska (Danylo Halytsky Lviv National Medical University, 2018)
Aim. Evaluate the contribution of non-genetic and genetic factors to the occurrence of fading pregnancy at the terms of less / more than 12 weeks of gestation.